Media‐Induced Elevation as a Means of Enhancing Feelings of Intergroup Connectedness. (March 2015) - Oliver, Mary Beth; Kim, Keunyeong; Hoewe, Jennifer; Chung, Mun‐Young; Ash, Erin; Woolley, Julia K.; Shade, Drew D.; Mastro, Dana; Tukachinsky, Riva
<x xml:space="preserve">Abstract</x> The majority of research on media counter‐stereotyping of race/ethnicity has tended to employ positive portrayals or counter‐stereotypical exemplars as a primary strategy in eliciting positive attitudes among White participants. In contrast, this article reports the results of an experiment on the unique role of affective responses to media messages as a mechanism in inducing greater feelings of connectedness with a diversity of racial/ethnic groups. Our focus is on the affective response of elevation specifically, which refers to feelings of being moved, touched, and inspired by images of people engaged in morally beautiful acts such as love, generosity, and kindness. Results show that the experience of elevation in response to inspiring videos was associated with heightened feelings of overlap between the self and humanity, with this overlap associated with greater feelings of connectedness with those from a diversity of racial/ethnic groups. This connection was also associated with more favorable attitudes.